The influence of internal and external factors on tax compliance MSMEs in Jakarta - Aulia, Muhammad Rafael Shauqi; Wijaya, Suparna (WIM Solusi Prima, 2024)
This study was conducted with the aim of finding empirical evidence related to the influence of internal factors, namely tax knowledge and tax socialization. As well as, external factors, namely tax sanctions on tax compliance of MSMEs in DKI Jakarta. This study uses a quantitative approach with primary data collected through questionnaires. Score measurement is measured using a Likert scale of 1-4. This study uses purposive sampling technique as a sampling technique. The sample used in this study was 100 respondents based on the results of the Lemeshow formula calculation. Data was processed using the Partial Least Square or PLS method and analyzed with the help of SmartPLS 3 software. The level of significance used in this study is 5% (0.05). The results of the study showed that tax knowledge has a significant positive effect on tax compliance of MSMEs in DKI Jakarta. Tax socialization also has a significant positive effect on tax compliance of MSMEs in DKI Jakarta. While tax sanctions have no effect on tax compliance of MSMEs in DKI Jakarta.